2002
DOI: 10.1046/j.1365-2044.2002.02361.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of videotape feedback on anaesthetists' performance while managing simulated anaesthetic crises: a multicentre study

Abstract: The aim of this study was to examine the performance of anaesthetists while managing simulated anaesthetic crises and to see whether their performance was improved by reviewing their own performances recorded on videotape. Thirty-two subjects from four hospitals were allocated randomly to one of two groups, with each subject completing five simulations in a single session. Individuals in the first group completed five simulations with only a short discussion between each simulation. Those in the second group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 13 publications
1
45
0
2
Order By: Relevance
“…As maintained by Fanning and Gaba (2007, p. 122), Bvideo playback may be useful for adding perspective to a simulation, to allow participants to see how they performed rather than how they thought they performed, and to help reduce hindsight bias in assessment of the scenario.T his study sets out to investigate what formulations like these might mean in terms of actual practice: in other words, how additional perspectives are made relevant in the debriefings; how participants orient to distinctions between appearances and experiences; and how students and facilitators assess the performances in the simulation scenarios. Previous research of videosupported debriefings has largely been carried out in the simulation research area, with a focus on the measured success or perceived effectiveness of this kind of feedback (e.g., Byrne et al 2002;Grant et al 2010;Hamilton et al 2011). In contrast, the present study investigates the interaction that takes place between students and facilitators as they jointly analyze and reflect on video recordings of the students' performances in the simulation scenarios during the investigated debriefings.…”
Section: Introductionmentioning
confidence: 99%
“…As maintained by Fanning and Gaba (2007, p. 122), Bvideo playback may be useful for adding perspective to a simulation, to allow participants to see how they performed rather than how they thought they performed, and to help reduce hindsight bias in assessment of the scenario.T his study sets out to investigate what formulations like these might mean in terms of actual practice: in other words, how additional perspectives are made relevant in the debriefings; how participants orient to distinctions between appearances and experiences; and how students and facilitators assess the performances in the simulation scenarios. Previous research of videosupported debriefings has largely been carried out in the simulation research area, with a focus on the measured success or perceived effectiveness of this kind of feedback (e.g., Byrne et al 2002;Grant et al 2010;Hamilton et al 2011). In contrast, the present study investigates the interaction that takes place between students and facilitators as they jointly analyze and reflect on video recordings of the students' performances in the simulation scenarios during the investigated debriefings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, literature suggests that debriefing is a social process where an understanding of emotion and thought processing is a vital element to the process. Current healthcare debriefing literature acknowledges the importance of reflection to increase retention of knowledge, skills, and attitudes [2][3][4][5][6][7][8][9]. This study highlighted that highrisk/high-stake debriefing are frequently undertaken immediate post-event, with some utilising more structured analysis using supplementary video technology.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have identified that effective facilitated debriefing sessions as a key step to promote deep insight and reflection to enhance learning and performance in healthcare [2][3][4][5][6][7][8][9]. Additionally, literature suggests that debriefing is a social process where an understanding of emotion and thought processing is a vital element to the process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations